(untitled) (TAMADDUN NURI JURNALI, 2024)
The article is devoted to the issues of studying the syntax section in the Russian and Uzbek languages. The article also discusses the comparison of simple common and non-common sentences. To study this topic, you need to know the members of sentences: subject, predicate, definition, circumstance, object.